Blood supply sufficiency and safety management in Iran during the COVID‐19 outbreak. Issue 2 (30th September 2020) - Maghsudlu, Mahtab; Eshghi, Peyman; Amini Kafi‐Abad, Sedigheh; Sedaghat, Abbas; Ranjbaran, Hossein; Mohammadi, Saeed; Tabatabai, Seyed Morteza
Abstract : Background: COVID‐19 first appeared in Iran on 19 February 2020, and then spread rapidly over the country. In this article, we review the action plan of the Iranian Blood Transfusion Organization with respect to this disease. Method and materials: We collected data on blood donations and RBC inventory for the first 8 weeks of the outbreak. We also evaluated the trend of blood donations and RBC inventory and compared them with the data of the past year. We include a summary of actions taken by the National Committee on Management of COVID‐19 outbreak. Results: Blood donations decreased from 33 275 to 23 465 units during the first 2 weeks of the outbreak with a corresponding decrease in the RBC inventory. But after that, donations gradually increased from 23 465 to 29 665 units. RBC inventory levels improved at the same time. Then, the Iranian New Year's holiday resulted in another downward trend. After the holiday, blood donations revived, along with the RBC inventory. Discussion: Although it appears that this virus cannot be transmitted through transfusion, changes in lifestyle had a significant impact on reducing blood supply. Following implemented measures, we saw an upward trend in blood donations and an adequate supply of RBC units in blood centres, helped by a reduction in demand by hospitals. Blood centres need to be more prepared to manage future viral disasters, especially in case of transfusion‐transmissible infections.